THE TAX PAYERS RESPONSE TO ZAKAT AS ADEDUCTION OF INCOME TAX (Study in KPP Office in Bandar Lampung City in 2018) - Budiarto, Dian Ahmad; Darmawan, Jaka (Prosiding International conference on Information Technology and Business (ICITB), 2018)
This study aims to examine and explain the provisions of zakat to reduce taxable income to taxpayers and to explain the response of taxpayers to zakat as a deduction from taxable income in the Tax Service Office (KPP) in Bandar Lampung City. The research method in this study is descriptive and explanative (analytic). The population in this study is 246,758 taxpayer taxpayers in Bandar Lampung. The sample in this study were 70 taxpayers. The sampling technique is by incidental sampling technique. The data analysis technique used in this study is simple linear regression analysis and test coefficient of determination. The results showed that Adjustted R Square is 0.321 or 32.1% which means that the independent variable (taxpayer response) can explain the dependent variable (Accounting Conservatism as tax deduction income) is 32.1% and the remaining 67.9% is explained by other factors not proposed by this study. Hypothesis test results, show the results that there is a significant influence between the response of the taxpayer to zakat as a deduction of income tax. Testing uses the SPSS version 21 tool. Keywords: Zakat as a deduction for income tax